The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40259-017-0243-4
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Application and Impact of MicroRNAs as Therapies for Skin Disease

Abstract: The advent of RNA interference (RNAi) technology has profoundly impacted molecular biology research and medicine but has also advanced the field of skin care. Both effector molecules of RNAi, short-interfering RNA molecules and microRNAs (miRNAs), have been explored for their relative impact and utility for treating a variety of skin conditions. These post-transcriptional RNA regulatory molecules down-modulate protein expression through targeting of the 3′ untranslated regions of messenger RNAs, leading to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…Among these, microRNA arrays are broadly used in research, including evaluating topical ingredients by utilizing real-time RT-PCR [ 17 , 19 , 20 ]. Finally, microRNAs in human skin aging have been reviewed recently along with the advances and applications of microRNAs as therapies for skin diseases like psoriasis [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, microRNA arrays are broadly used in research, including evaluating topical ingredients by utilizing real-time RT-PCR [ 17 , 19 , 20 ]. Finally, microRNAs in human skin aging have been reviewed recently along with the advances and applications of microRNAs as therapies for skin diseases like psoriasis [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is interesting to find in this study that all three microRNAs identified were upregulated by BlendIP. Many studies that have examined different microRNAs from the skin showed that microRNAs are associated with skin cancers or skin diseases [ 18 , 19 , 20 , 38 , 39 ]. Finally, it is also important to understand how microRNAs keep the skin healthy, to prevent skin aging.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have supported that miRNAs are involved in morphogenesis and homeostasis of the skin and its appendages [6]. The miRNAs act as essential regulators of differentiation, proliferation, and survival at the cellular level of skin cells including keratinocytes [7,8] suggesting the role of miRNA in epidermal barrier integrity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known about cells with accelerated division behavior (e.g., tumor cells) that transiently released miRNAs are as well eliminated faster, making them less suitable as therapeutic target structures [11]. Various experimental approaches have been described regarding the use of miRNA-based therapies for the treatment of skin tumors, but there have been only a few clinical investigations so far [12, 13].…”
Section: Introductionmentioning
confidence: 99%